Phylogeny of selected babblers (Family : Timaliidae) inferred from mtdna cytochrome oxidase I (COI) gene - Hii, Frances Dai Sze (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study on phylogeny of eight species of babblers (Family: Timaliidae) in Sarawak by using mitochondrial DNA (mtDNA) cytochrome oxidase I (COI) gene was conducted. The samples were taken from both fresh and also voucher specimens that were available in UNIMAS. Four phylogenetic trees were constructed by using four different methods namely, Neighbour-Joining (NJ), Maximum Parsimony (MP), Maximum Likelihood (ML) and Bayesian inferences in this study. The ML and Bayesian trees showed that Timaliidae can be grouped into two groups that is group 1, genus Stachyris, and group 2, which consist of Pellorneum, Trichastoma, Malacocincla and Malacopteron genera. This showed that Pellorneum, Trichastoma, Malacocincla and Malacopteron are closely related compared to genus Stachyris. COI is a good genetic marker which can detect intraspecific variation within species and the relationship of the individuals by comparing the genetic divergence and the length of tree.